Familial adenomatous polyposis associated with multiple adrenal adenomas in a patient with a rare 3′ APC mutation. Issue 1 (1st January 1999) - Kartheuser, Alex; Walon, Corinne; West, Sarah; Breukel, Cor; Detry, Roger; Gribomont, Anne-Catherine; Hamzehloei, Tayebeh; Hoang, Pierre; Maiter, Dominique; Pringot, Jacques; Rahier, Jacques; Khan, P Meera; et al.
Abstract : Familial adenomatous polyposis (FAP) is characterised by hundreds of colorectal adenomas. Endocrine neoplasms have occasionally been reported, as have gastric polyps, which are usually hamartomatous in the fundus of the stomach and adenomatous in the antrum. A 57 year old man with colorectal, gastric, and periampullary adenomatous polyposis, in association with three bilateral adrenocortical adenomas, is presented. Mutation screening showed a 5960delA germline mutation in the adenomatous polyposis coli (APC) gene predicted to lead to a premature stop codon. This mutation was found in three of the four children of the patient. Western blot analysis of a lymphoblastoid cell line derived from the patient failed to detect any truncated APC polypeptide. This rare 3′ mutation is responsible for an unusually complex and late onset phenotype of FAP.